Obstetrical management of fetus with intra uterine growth restriction (IUGR) and late IUGR - Ferrazzi, Enrico; Casati, Daniela; Zullino, Sara; Rosti, Eleonora (Acta Biomedica Atenei Parmensis, 2015)
In this article we evaluated an important complication of pregnancy, the fetal growth restriction (IUGR). IUGR is defined as an estimated fetal weight of fetal abdominal circumference below the 10th centile measured by ultrasound according to local standards. We present the prenatal surveillance, the screening tests for late IUGR and the new diagnostic examinations, to establish the best prevention system for IUGR and late IUGR.